Ringed, Bearded, and Ribbon Seal Vocalizations North of Barrow, Alaska: Seasonal Presence and Relationship with Sea Ice - Jones, Joshua M.; Thayre, Bruce J.; Roth, Ethan H.; Mahoney, Michael; Sia, Ian; Merculief, Kayla; Jackson, Christine; Zeller, Clarissa; Clare, Mamie; Bacon, Austin; Weaver, Samantha; Gentes, Zoe; et al. (ARCTIC, 2014)
The acoustic repertoires of ringed, bearded, and ribbon seals are described, along with their seasonal occurrence and relationship to sea ice concentration. Acoustic recordings were made between September and June over three years (2006 – 09) along the continental slope break in the Chukchi Sea, 120 km north-northwest of Barrow, Alaska. Vocalizations of ringed and bearded seals occurred in winter and during periods of 80% – 100% ice cover but were mostly absent during open water periods. The presence of ringed and bearded seal calls throughout winter and spring suggests that some portion of their population is overwintering. Analysis of the repertoire of ringed and bearded seal calls shows seasonal variation. Ringed seal calls are primarily barks in winter and yelps in spring, while bearded seal moans increase during spring. Ribbon seal calls were detected only in the fall of 2008 during the open water period. The repertoire of known ribbon seal vocalizations was expanded to include three additional calls, and two stereotyped call sequences were common. Retrospective analyses of ringed seal recordings from 1982 and ribbon seal recordings from 1967 showed a high degree of stability in call repertoire across large spatial and temporal scales. Le répertoire acoustique des phoques annelés, des phoques barbus et des phoques à bandes sont décrits, de même que leur présence saisonnière et leur rapport avec la concentration de glace de mer. Des enregistrements acoustiques ont été effectués entre septembre et juin sur une période de trois ans (2006 – 2009), le long de la rupture de la pente continentale, dans la mer des Tchouktches, à 120 km au nord-nord-ouest de Barrow, en Alaska. Les vocalisations de phoques annelés et de phoques barbus étaient présentes pendant l’hiver et pendant les périodes où la concentration de glace était de 80 % à 100 %, mais elles se faisaient rares pendant les périodes d’eau libre. La présence des cris de phoques annelés et de phoques barbus tout au long de l’hiver et du printemps suggère ...